Fermentasi Kombinasi Nanas, Air Kelapa, Minyak Ikan, Minyak Cumi Untuk Meningkatkan Kelangsungan Hidup Udang Vaname (Litopenaeus vannamei) - Revindra Nurdian Zahrani; Valent Keyllafara Simon; Dwi Ramadya Risqiana Putri (Jurnal Akuakultur Rawa Indonesia, 2026)
This study aims to evaluate the effect of a combination of pineapple, coconut water, fish oil, and squid oil fermentation on the Survival Rate (SR) and Feed Conversion Ratio (FCR) of intensively farmed whiteleg shrimp (Litopenaeus vannamei). The study was conducted at the Marine Cultivation Installation for three months (February–April 2025). PL-12 stage fry were stocked into a 1,300 m² HDPE pond with a stocking density of 210,000 individuals. The fermentation mixture consisted of 500 g pineapple, 500 mL coconut water, 50 mL fish oil, and 50 mL squid oil, which were fermented for 3–5 days before being mixed into commercial pellets. The results showed that the FCR value was 1.37 and the SR was 96.4%. These values ​​indicate high feed efficiency and optimal survival. The combination of natural ingredients through fermentation can increase feed digestibility, improve hepatopancreatic health, and enhance shrimp resilience to environmental stress. Therefore, this fermented combination of natural ingredients has the potential to be a sustainable functional feed innovation in intensive shrimp farming systems.